Some Economic Dimensions of Sustainable Development - Baicu, Claudia Gabriela (Journal of Economic Development, Environment and People, 2016)
We are living today in a world of huge challenges, deep interconnections, profound mutations and global risks under the impact of several factors among which climate change, innovation, increased competition or evolution of technology could be mentioned.....